Pengaruh Content Marketing Shopee Live dan Gamification terhadap Customer Engagement di Kecamatan Medan Johor - Humaira, Sahla; Salqaura, Siti Alhamra; Tarigan, Eka Dewi Setia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine the influence of Shopee Live Content Marketing and Gamification on Customer Engagement among Shopee users in the Medan Johor District. This study employs a quantitative associative approach with 100 respondents selected through stratified random sampling. Data were collected using an online questionnaire and analyzed through multiple linear regression. The results indicate that Shopee Live Content Marketing (β = 0.491; p = 0.000) and Gamification (β = 0.403; p = 0.000) have a significant effect on Customer Engagement. Simultaneously, both variables significantly influence Customer Engagement (F = 80.347; p = 0.000) with an R² value of 0.616. These findings suggest that interactive content strategies and gamification are effective in enhancing customer engagement.